The villain in Spiderman movie I: a deconstructive analysis - Tino Agus Salim (Jurnal Linguistik Terapan, 2012)
This article reviews on how deconstructive reading strategy plays an important role to reveal meanings in the movie that are tried to hide. Analyzing movie is an important study to do as we can gain a lot of advantages from the movie such as ideas, concepts, and values of life. One and the first most successful film based on a comic book is Spiderman Movie I with the villain named Green Goblin. This article focuses on analyzing Green Goblin's characterizations from the perspective of Deconstruction. The character of Green Goblin will be observed by using Propp's Morphology of Folk Tale and later dismantled by deconstructive reading strategy. Green Goblin, in this particular movie, is always considered as a bad guy. Ignoring the motives or causes of being Green Goblin leads viewers to judge that he is a villain in New York City and must be eliminated. Nevertheless, by using deconstructive reading strategy, the idea of Green Goblin will be dismantled and built again to find some undecidable meanings.